2023
DOI: 10.1021/acs.inorgchem.3c00473
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Detection of Iodine Species by a Thorium-Based Metal–Organic Framework

Abstract: Actinide-bearing metal−organic frameworks (MOFs) encompass intriguing structures and properties, but the radioactivity of actinide cripples their applications. Herein, we have constructed a new thorium-based MOF (Th-BDAT) as a bifunctional platform for the adsorption and detection of radioiodine, a more radioactive fission product that can readily spread through the atmosphere in its molecular form or via solution as anionic species. The iodine capture within the framework of Th-BDAT from both the vapor phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…34,69 This indicates that the interaction of adsorbed iodine species and the polar framework of compound 1 has occurred, where the iodine captured within the inner cavity of compound 1 has been reduced into polyiodine species, which is still close to general predictions for the charge transfer between the adsorbed iodine and electron-rich binding sites from the L ligand molecule. 33,34,70,71 Moreover, due to the presence of the iodine polyanionic species, as expected, it is found that the value of powder electrical conductivity is rising from 1.5 × 10 −5 S cm −1 for pristine 1 to 2.6 × 10 −4 S cm −1 for the iodinated I 2 @compound 1 . Mechanistic insight for this iodine uptake reveals that the iodine molecules may be captured first by the high affinity soft binding sites within the inner cavity of compound 1 ’s framework; subsequently the iodine polyanionic species are generated by the charge transfer between the absorbed iodine molecules and the electron-rich sites in the framework.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…34,69 This indicates that the interaction of adsorbed iodine species and the polar framework of compound 1 has occurred, where the iodine captured within the inner cavity of compound 1 has been reduced into polyiodine species, which is still close to general predictions for the charge transfer between the adsorbed iodine and electron-rich binding sites from the L ligand molecule. 33,34,70,71 Moreover, due to the presence of the iodine polyanionic species, as expected, it is found that the value of powder electrical conductivity is rising from 1.5 × 10 −5 S cm −1 for pristine 1 to 2.6 × 10 −4 S cm −1 for the iodinated I 2 @compound 1 . Mechanistic insight for this iodine uptake reveals that the iodine molecules may be captured first by the high affinity soft binding sites within the inner cavity of compound 1 ’s framework; subsequently the iodine polyanionic species are generated by the charge transfer between the absorbed iodine molecules and the electron-rich sites in the framework.…”
Section: Resultssupporting
confidence: 74%
“…2b, the XPS spectra give two sets of energy signal bands at 631 eV and 619.5 eV for compound 1 after iodine vapor fumigation, corresponding to the binding energies of I 3d 3/2 and I 3d 5/2 orbitals for iodine molecular species, 1,34,68,69 respectively. Here, the signals in both I 3d 3/2 and I 3d 5/2 regions can be further fitted by double sets of two well-resolved peaks that allow for assigning to iodine neutral molecule (632.0 and 620.5 eV) and its polyanionic species (630.9 and 619.4 eV), 33 of which, based on the calculation for the integral areas of peaks, the uptake content is close to 28.6% in the former iodine molecule whereas it is near 71.4% in the latter polyanionic species. This means that an iodine disproportionation conversion may have occurred during the I 2 uptake process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all the above-mentioned cases, surface as well as inclusion-based iodine transfer is likely to occur even with a less porous nature of the framework . From the results of multiphase iodine transfer studies conducted with 1 and 2 , it can be inferred that the uptake values in this work are better than many MOFs, POPs, and zeolites (Table S1) , For instance, the values of vapor phase iodine mass transfer for a T -SCNU-Z6 and a W -SCNU-Z6 are 2.05 g g –1 and 5.04 g g –1 , respectively, whereas, those for HSB-W8 and Co-IPT-IBA are 2.32 g g –1 , and 2.88 g g –1 , respectively. Compared to this, ionic iodine transfer studies in the aqueous phase are rare.…”
Section: Resultsmentioning
confidence: 80%
“…MOFs are a distinctive class of porous materials that have widely been used for several applications like the detection of small hazardous molecules, capturing and sequestering small molecules, heterogeneous catalysis, energy storage, gas separation, and water splitting and harvesting, etc. Thus, the capture of molecular and ionic iodines has been demonstrated to a good extent by these materials. However, only a handful of reports have been published with adequate iodine capture values from the vapor phase as well as the solution phase. Most of the robust and stable materials that are suitable for such iodine capture studies were synthesized under drastic conditions. For instance, MOFs and COFs are synthesized solvothermally, under high temperature and vacuum conditions, or through microwave treatment or by the use of additional reagents, like modulators and acids/bases. It is known that taking a methodology to perform a large-scale application requires great effort, for which there is a requirement of simplification in synthetic methods.…”
Section: Introductionmentioning
confidence: 99%